Examining Folk-Economic Beliefs among Students in Prague - Thomas, Reiter (2020)
This thesis aimed to test the theoretical predictions of the existence of folk-economic beliefs and whether they can be dissolved with a higher economic knowledge. The main added-value of the paper is the empirical evidence of folk-economic beliefs and how they can be dissolved through economic knowledge. Folk-economic discusses the rudimental beliefs about economics and economic phenomena. Folk-economic beliefs are important to correct since in democratic systems these beliefs could lead to costly errors with unintended consequences. The field of folk economics has been developed mainly through the findings of Rubin (2002), Boyer and Petersen (2018) and Caplan (2006). To test the hypothesis, this paper conducted a survey among international students in Prague with 87 participants. The participants were asked to state their positions on different economic topics, such as immigration or international trade. The results showed that a large portion of the sample held folk-economic beliefs on most of the statements. It also showed how the answers for “low” and “high” knowledge participants systematically differed. For the data, the model showed how these beliefs can be corrected through higher economic knowledge and additional semesters of economic studies. Due to the insignificance of the estimates and small sample size, this thesis could not make conclusions about the effects on the population of students in Prague.